CROSS-CULTURAL BUSINESS NEGOTIATIONS Case: Finnish, Spanish and Portuguese Business Negotiations - Timo, Minna (My University, 2005)
The main objective of the present study is to examine whether national culture affects the negotiating behaviour of the Finnish, Spanish and Portuguese businessmen, and to understand as well as explain how it shows in negotiations. Based on existing theory, the variables explaining negotiation behaviour as well as the cultural variables likely to affect negotiating behaviour were identified. The study utilises the Bird and Metcalf’s refinement of the Weiss and Stripp negotiation framework, which form the twelve negotiation variables for this study. The negotiating variables are linked to the Hofstede’s four variables of culture. Based on the linkages, propositions are developed concerning expected negotiating behaviour of the Finnish, Spanish and Portuguese negotiators. The validity of the propositions was examined em-pirically by a survey. The study is a quantitative study and the differences and similarities between the nego-tiating behaviour of the Finnish, Spanish and Portuguese businessmen were revealed by comparing the hypothesised negotiating behaviour of the respective countries’ negotia-tors. The measurement instrument of the study was examined and developed further using Cronbach’s alfa, and the twelve hypotheses tested using t-test, which measures the difference between means. From the twelve hypotheses, eight (1, 2, 5, 6, 9, 10, 11 and 12) were not supported, one hypothesis (4) was moderately supported and three hypotheses (3, 7 and 8) were supported by the study.
Keywords: Cross-cultural business negotiations; negotiating behaviour; intercultural; international; cross-cultural; fi=Markkinointi|en=Marketing|; fi=Kansainvälisen yritystoiminnan koulutusohjelma|